An investigation into efl high school teachers' perspectives on and practice of using prescribed lesson plans within the setting of the junior high school instruction : - Nguyễn, Thanh Bình Tâm (Đại học Cần Thơ, 2013)
The thesis entitled "An investigation into efl high school teachers' perspectives on and practice of using prescribed lesson plans within the setting of the junior high school instruction" was conducted by a descriptive study to investigate EFL high school teachers' perspectives on and practice of using prescribed lesson plans within the setting of the junior high school instruction.